The Holy Month of Ramadan: Mass-Gathering Event Implications for Hospital Surge Capacity Planning in Saudi Arabia. Issue 4 (30th August 2021) - Almalki, Yousef; Hart, Alexander; Issa, Fadi; Hertelendy, Attila J.; Mahon, Selwyn; Voskanyan, Amalia; Ciottone, Gregory R.
Abstract: Objectives: The goal of this study is to determine the impact of the Holy Month of Ramadan on emergency department (ED) and hospital resource utilization in comparison to the time of Hajj and the rest of the year, so as to better define future resource needs of hospitals responding to events of this large size and duration. Methods: A retrospective chart review was conducted of electronic medical records, ED visits, and hospital admissions during Ramadan, Hajj, and all other months over a three-year period on the Hijra calendar (1438-1440) or Gregorian (2016-2019). Primary outcomes were the change in the number of ED visits, hospital admissions, and intensive care unit (ICU) admissions during Ramadan in comparison to during Hajj and other months. Secondary outcomes included mortality; number of surgeries by specialty; and admissions to cardiac, respiratory, orthopedic, and neurosurgery wards. Results: During the three years, ED visits increased during Ramadan by 83.0%, 74.8%, and 40.3%, respectively, when compared to non-Hajj, non-Ramadan months. Hospital admissions rose by 21.05%, 50.96% and 48.22%. Combined ED and in-hospital mortality rose by 15.21%, 21.47%, and 1.39%. While there was a large increase in ICU admissions during Ramadan of 1440 (May 2019), this was not a trend seen in other years. Despite there only being two years of data for comparison, there was a trend towards increased admissions to all specialty wards. There was an average 46.69% increase in admissions to the general surgery ward during Ramadan months compared to other months, a 31.06% increase in admissions to the orthopedic surgery ward, and a 44.05% increase in admissions to the cardiac care unit. Conclusions: Ramadan is associated with a significant increase in the population of Makkah (Mecca), Saudi Arabia. Despite this study only focusing on a three-year period, and some variables with only two years of data available, it demonstrates a significant increase in ED visits, hospital admissions, and mortality during Ramadan compared to non-Hajj/non-Ramadan months. During mass gatherings of this size, it would benefit local and regional hospital systems to devote increased resources to patient care, especially to the ED, to prevent morbidity and mortality.